The Association between Dapagliflozin Use and the Risk of Post-Contrast Acute Kidney Injury in Patients with Type 2 Diabetes and Chronic Kidney Disease: A Propensity-Matched Analysis - Tao Liu; Xinwen Jian; Li Li; Shan Chu; Zeyuan Fan (Karger Publishers, 2023)
Introduction: This study aimed to investigate the effect of dapagliflozin in preventing post-contrast acute kidney injury (PC-AKI) in patients with type 2 diabetes (T2DM) and chronic kidney disease (CKD) who underwent an elective coronary procedure. Methods: Data of patients with T2DM and CKD undergoing an elective coronary procedure at Civil Aviation General Hospital from October 2020 to April 2023 were collected from the electronic medical records. Based on dapagliflozin usage, patients were classified as dapagliflozin users and nonusers. 1:1 nearest-neighbor propensity matching was performed to compare dapagliflozin users with nonusers. The primary endpoint was the first PC-AKI observed. Univariate and multivariate COX regression models were used to determine the independent risk/preventive factors for PC-AKI. Thereafter, subgroup analyses were performed to evaluate the interaction between subgroup and dapagliflozin usage. Changes in the serum creatinine (SCr) and cystatin C (CysC) levels were monitored at 24 h, 48 h, and 72 h after the procedure. Results: 256 pairs (256 dapagliflozin users in the dapagliflozin group and 256 dapagliflozin nonusers in the control group) were identified in the cohort. The incidence of PC-AKI in dapagliflozin group (10.9%) was lower than that in control group (22.3%). COX regression analyses showed that dapagliflozin use was associated with a lower risk of PC-AKI (HR 0.81, 95% CI: 0.69-0.95, p = 0.01) after adjustment for covariates. In the subgroup analyses, similar HRs of the dapagliflozin usage on the PC-AKI outcome were observed in patients across different patients' characteristics which revealed its consistent benefit of preventing PC-AKI. The estimated glomerular filtration rate levels at post-48 h and 72 h were significant higher in the dapagliflozin group than those in the control group, while levels of SCr (post-48 h and 72 h) and CysC (post-24 h and 48 h) in the dapagliflozin group were lower compared with the control group. Conclusion: Our findings suggest dapagliflozin effectively decreases PC-AKI risk and exerts reno-protective effects in patients with T2DM and CKD undergoing an elective coronary procedure.